2016
DOI: 10.1111/jon.12411
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study to Assess Brain MRI Change and Disease Progression in Multiple Sclerosis Clinical Practice—The MS‐MRIUS Study

Abstract: BACKGROUND & PURPOSETo describe methodology, interim baseline, and longitudinal magnetic resonance imaging (MRI) acquisition parameter characteristics of the multiple sclerosis clinical outcome and MRI in the United States (MS‐MRIUS).MATERIAL & METHODSThe MS‐MRIUS is an ongoing longitudinal and retrospective study of MS patients on fingolimod. Clinical and brain MRI image scan data were collected from 600 patients across 33 MS centers in the United States. MRI brain outcomes included change in whole‐brain volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…MS‐MRIUS is one of the first studies to collect MRI and clinical data, including data on brain atrophy, from multiple MS centers that followed patients in routine clinical practice, in order to provide evidence of fingolimod's impact on the four key measures of disease activity (relapses, lesions, disability, and brain atrophy) in a real‐world setting …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MS‐MRIUS is one of the first studies to collect MRI and clinical data, including data on brain atrophy, from multiple MS centers that followed patients in routine clinical practice, in order to provide evidence of fingolimod's impact on the four key measures of disease activity (relapses, lesions, disability, and brain atrophy) in a real‐world setting …”
Section: Discussionmentioning
confidence: 99%
“…MS‐MRIUS is a multicenter, observational, longitudinal cohort study in routine clinical practice that retrospectively analyzed 590 relapsing‐remitting MS (RRMS) patients who initiated on fingolimod .5 mg . Patients with RRMS in whom fingolimod treatment were initiated de novo were identified between August 2014 and June 2016 from 33 participating MS centers across the USA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodologic approach and design of this retrospective study have been previously reported. 18 Briefly, clinical information and digital brain MR imaging image data were retrospectively collected from 33 participating academic and nonacademic MS centers across the United States and integrated into a central research data base.…”
Section: Methodsmentioning
confidence: 99%